Using High Performance Computing for Detecting Duplicate, Similar and Related Images in a Large Data Collection - Arora, Ritu; Trelogan, Jessica; Ba, Trung Nguyen (Conquering Big Data with High Performance Computing, 2016)
The detection of duplicate and related content is a critical data curation task in the context of digital research collections. This task can be challenging, if not impossible, to do manually in large, unstructured, and noisy collections. While there are many automated solutions for deduplicating data that contain large numbers of identical copies, it can be particularly difficult to find a solution for identifying redundancy within image-heavy collections that have evolved over a long span of time or have been created collaboratively by large groups. These types of collections, especially in academic research settings, in which the datasets are used for a wide range of publication, teaching, and research activities, can be characterized by (1) large numbers of heterogeneous file formats, (2) repetitive photographic documentation of the same subjects in a variety of conditions (3) multiple copies or subsets of images with slight modifications (e.g., cropping or color-balancing) and (4) complex file structures and naming conventions that may not be consistent throughout. In this chapter, we present a scalable and automated approach for detecting duplicate, similar, and related images, along with subimages, in digital data collections. Our approach can assist in efficiently managing redundancy in any large image collection on High Performance Computing (HPC) resources. While we illustrate the approach with a large archaeological collection, it is domain-neutral and is widely applicable to image-heavy collections within any HPC platform that has general-purpose processors.